Indonesian College Students’ Perception toward Language Online Learning Before and During COVID-19 Pandemic - Rahmayanti, Putu; Suwastini, Ni Komang Arie; Dantes, Gede Rasben; Kultsum, Ummi (Journal of Education Technology, 2022)
Integration of technology in the teaching and learning process brings innovation where a learning process can be conducted virtually despite time and place boundaries. Online learning as the integration of learning and technology is used as the primary strategy to continue the teaching and learning process due to the Covid-19 outbreak. This study aims to analyze student perceptions of online learning before and during the COVID-19 pandemic. This research is a descriptive research with a qualitative approach. The results showed that the students had negative and positive perceptions of online learning before and during the pandemic. Before the pandemic, the students emphasized exploring the materials, while the students emphasized flexibility in learning during the pandemic. Meanwhile, negative perceptions are shown through the loss of direct communication between teachers and students. During the pandemic, students emphasized the flexibility aspect of the online learning mode. However, negative perceptions also emerged, namely the abundance of online tasks and the difficulties of using e-learning. Various challenges of online learning were also found during the pandemic compared to before the outbreak. For example in addition to inadequate internet connections and gadgets, anxiety problems due to the workload and less appropriate learning plan also arose. It can be seen that online learning before and during the outbreak experienced dynamics, so teachers and students must be encouraged to be more adaptive in dealing with changes in their learning.